DESIGNING “LEARY” IN VOCABULARIES TEACHING LEARNING FOR BEGINNER - Agustina, Ulfa Wulan; Amala, Nur (JoEMS (Journal of Education and Management Studies), 2021)
English is an international language. English is the language of communication in the globalized world, so that almost no country does not learn and use English as the language of international communication. The objective of the research is to designing LeaRy (Learn Vocabulary) for beginner level of English learners. In this research, the researcher used Research and Development (R&D) methods. This research procedure adapts the ADDIE development model which consists of five stages which include analysis, design, development, implementation and evaluation. The researcher used observation and questionnaire to collect the data. The researcher did research and field testing to the 21 students in Al-Lathifiyyah 1 females Islamic Boarding House. The result of material validation is 3.3 points and categorized as good quality. Then, the result of media validation is also categorized as good quality in 3.2 points. In addition, the result of user validation is 4.7 points and categorized as good quality. Therefore, LeaRy learning media is a good learning media to learn English vocabulary, especially in spell vocabulary and Elnglish pronunciation.